Desirability function analysis (DFA) in multiple responses optimization of abrasive water jet cutting process - Subramanian, Sathiyaraj; Sendrayan, Venkatesan; Devadass, Raja; Jayavel, Gokul; Oommen, Jithin Y.; Biju, Diaz K. (AIP conference proceedings, 2024)
The machinability of nickel aluminium bronze with abrasive water jet machining technique is the subject of this paper. Three separate parameters are used in this machining process, including standoff distance at three different levels, transverse speed of abrasive flow rate, and water jet pressure. The examination of kerf width, surface roughness, and material removal rate (MRR) forms the basis of the machining. Examining surface morphology and material removal techniques also include using images from scanning electron microscopes (SEM), optical images, and surface roughness images. Water jet pressure and velocity were determined to be most influential factors.